(untitled) - Iannucci, Joen M. (Missouri, 2006)
Inside you’ll find the essential principles of radiation and the technical skills necessary for the safe and effective use of radiation in the dental office. The book serves as both a textbook and training manual by providing comprehensive coverage of basic theory and complete technical instruction. Procedures are presented in a detailed step-by-step format with accompanying illustrations, rationales, and charting notes. Includes a new interactive student CD-ROM. * Chapters are short with topics separated into easy-to-digest sections. * Content is divided into six parts, covering all necessary aspects of dental radiography * Step-by-step procedures throughout the chapters include rationales and charting notes along with essential illustrations and photos to demonstrate techniques properly. * Quiz questions for each chapter help students assess knowledge and comprehension. * Example boxes are used throughout the chapters to further explain a process or why it is performed a certain way.
Keywords: Dental,Răng